The Impact of Use Proposed Educational Software in Raising a Number of Cognitive Skills for Children with Moderate Intellectual Disabilities: أثر استخدام برمجية تعليمية مقترحة في رفع عدد من المهارات الإدراكية للأطفال من ذوي الإعاقة الذهنية المتوسطة - Mohamed Badawi Mostafa - Samani Abdul Muttalib Ahmed - Talaat Mohieddin Wahbi (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
Children with Mental disabilities face big challenges in the process of education and training through traditional educational systems and methods, making them useless and cumbersome for them and for those who train them also does not support the achievement of educational and training objectives that reflect the aims of education or training. The Objective of this study is to identify the challenges and difficulties faced by children with mental disabilities ranging from 6 to 11 years of age in the process of teaching them some cognitive skills and then developing educational software based on multimedia applications to teach them how to identify some basic skills such as measurement of sizes, colors and Basic calculation process. This study was based on the experimental method where the sample of the study consisted of two groups, one experimental and the other an Control Where the experimental group consisted of 7 children and their intelligence ranged between 55- 70 While the control group consisted of 7 children and their intelligence ranged from 55- 70. The results of the study showed how effective of the software in raising the level of cognitive ability in distinguishing the skills to be raised and the teaching of the sample where the percentage of correct responses ranged between 85- 90% for the experimental group in the measurement of the distance of all activities that have been measured the effectiveness of the software in its education.